Exposures and health impact for bicycle and electric scooter commuters in Taipei. (February 2021) - Wu, Tzong-Gang; Chang, Jung-Chi; Huang, Sheng-Hsiu; Lin, Wan-Yu; Chan, Chang-Chuan; Wu, Chang-Fu
Highlights: Riding on minor roads reduced exposure to BTEXs and PM2.5 . Scooter commuters were exposed to more BTEXs than bicycle commuters. Due to their ubiquity, scooters contributed the most to PM2.5 . Single-pollutant health impact modeling may result in underestimation. Abstract: Bicycle and scooter commuters are known to expose to more traffic-related pollutants. Benzene, toluene, ethylbenzene, xylenes (BTEXs), and PM2.5 were measured along four routes during rush hour and non-rush hour periods by cyclists and motorcyclists in Taipei, Taiwan. The health impacts were also evaluated using health impact modeling (HIM) approach. The average exposures of total BTEX and PM2.5 were 20.07 ppb and 23.27 μg/m 3 for the cyclists and 33.96 ppb and 27.65 μg/m 3 for the motorcyclists, respectively. Riding on an "alternative" route resulted in lower exposure. Scooters could contribute more to PM2.5 exposure than buses/trucks and passenger cars. Cyclists could have a lower risk of all-cause mortality and a single-pollutant HIM was found to result in underestimations. In conclusion, the number of scooters in traffic should be reduced, and commuters should be encouraged to shift from gasoline scooters to bicycles to reduce air pollution.